2016
DOI: 10.1002/cnm.2838
|View full text |Cite
|
Sign up to set email alerts
|

A quasi‐3D wire approach to model pulmonary airflow in human airways

Abstract: The models used for modeling the airflow in the human airways are either 0-dimensional compartmental or full 3-dimensional (3D) computational fluid dynamics (CFD) models. In the former, airways are treated as compartments, and the computations are performed with several assumptions, thereby generating a low-fidelity solution. The CFD method displays extremely high fidelity since the solution is obtained by solving the conservation equations in a physiologically consistent geometry. However, CFD models (1) requ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
48
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 34 publications
(49 citation statements)
references
References 13 publications
1
48
0
Order By: Relevance
“…ARDS often remain non-specific and subsequently under-diagnosed or under-treated due to the lack of knowledge concerning the pathophysiology of lung injury, pulmonary complications and repair mechanisms. Kannan et al have performed very high fidelity 2D and 3D simulations for accurately and efficiently predicting and quantifying local and global injuries (caused by trauma, hemorrhages, blasts) for organs like the brain and the lung [7,8]. They were able to noninvasively "numerically penetrating" the tissues, and reconstruct the optical properties the presence of water, oxygenated and de-oxygenated blood [7,8].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…ARDS often remain non-specific and subsequently under-diagnosed or under-treated due to the lack of knowledge concerning the pathophysiology of lung injury, pulmonary complications and repair mechanisms. Kannan et al have performed very high fidelity 2D and 3D simulations for accurately and efficiently predicting and quantifying local and global injuries (caused by trauma, hemorrhages, blasts) for organs like the brain and the lung [7,8]. They were able to noninvasively "numerically penetrating" the tissues, and reconstruct the optical properties the presence of water, oxygenated and de-oxygenated blood [7,8].…”
Section: Introductionmentioning
confidence: 99%
“…Kannan et al have performed very high fidelity 2D and 3D simulations for accurately and efficiently predicting and quantifying local and global injuries (caused by trauma, hemorrhages, blasts) for organs like the brain and the lung [7,8]. They were able to noninvasively "numerically penetrating" the tissues, and reconstruct the optical properties the presence of water, oxygenated and de-oxygenated blood [7,8]. These numerical noninvasive measurements are then used to predict the extent and severity of the organ hemorrhage/injury.…”
Section: Introductionmentioning
confidence: 99%
“…However, Kannan et al have revealed that the deposition of particle substance to airway and lung depends on many factors including the property of the particle, anatomical geometry of the airway, and respiratory pattern [46, 47]. And it may be possible to obtain more analysis from the computational Euler-Langrangian particle delivery approach of Kannan et al [47].…”
Section: Discussionmentioning
confidence: 99%
“…The Office of Generic Drugs (OGD) in the Center for Drug Evaluation and Research at the FDA has funded two grants related to the in silico modeling of OIDPs prior to fiscal year 2018 using funds obtained from the Generic Drug User Fee Amendments regulatory science program . In 2014, a grant titled “A Predictive Multiscale Computational Tool for Simulation of Lung Absorption and Pharmacokinetics and Optimization of Pulmonary Drug Delivery” was awarded to CFD Research Corporation for the development of an integrated CFD‐PBPK lung model, which has been previously described in this article . The key gap that this grant addressed is the lack of PBPK models for OIDPs that take full advantage of CFD for its ability to both predict deposition and to capture the effects of mucociliary clearance.…”
Section: Future Directionsmentioning
confidence: 99%
“…Another area of potential improvement for lung PBPK models is mucociliary clearance methodology, where most models use a compartmental approach. Kannan and colleagues have addressed this issue in part by developing a Q3D methodology that is capable of local absorption prediction with much greater precision . A Generic Drug User Fee Amendments–funded continuation of this work has recently been announced by the OGD, which will involve the expansion of the Q3D model to include respiratory airways and the application of the Q3D methodology to other lung geometries…”
Section: Future Directionsmentioning
confidence: 99%